Quantum Computing: Unleashing the Potential of Qubits and Quantum Gates - Rahmani, Md Shibli (International Journal of Computer Sciences and Engineering, 2025)
The potential of quantum computing to revolutionize various industries and markets has been widely recognized. By utilizing the principles of quantum mechanics such as superposition and entanglement, quantum computers are capable of representing data and performing operations on them at an unprecedented speed. These unique features allow for solving complex problems that are practically impossible for classical computers to solve efficiently. This article provides an overview of the three layers of a quantum computer, which include the hardware layer, system software layer, and application layer. Moreover, it discusses the potential applications of quantum computing and explores possible research directions in the field of information systems.